The turning point of 1699 in Polish-Turkish relations and changes in the Polish nobility’s perception of the Orient. An attempt to highlight selected issues - Kurek, Jacek (Balcanica Posnaniensia. Acta et studia, 2003)
This article attempts to describe changes in the Polish nobility's perception of the Orient after the end of the long wars between the Polish-Lithuanian Commonwealth and the Ottoman Empire. The events of this period symbolise a transition from perceiving Turkey as a dangerous enemy to viewing it as an exotic and ‘tamed’ neighbour. The aim of the article is to show examples of this process based on literature, journalism and popular culture, e.g. proverbs. Attention is drawn to the growing acceptance of Oriental references in noble culture and the often friendly, curious view of the East. The analysis is based on literature from the period, press reports from „Kurier Polski”, letters and journalism from the early 18th century. The research shows that after 1699, the Polish nobility viewed the Orient as an element of their cultural identity. A fashion for Orientalism took hold, visible in music, clothing and customs.